Students’ Use of Translation Techniques: A Case of the 4th Semester Students of Universitas Peradaban - Akhmad Nur Cholis; Dwi Anggani Linggar Barati Anggani Linggar Barati (Universitas Negeri Semarang, 2022)
English is a medium of international communication and it is a bridge to communicate among people with different languages and cultures. Communication has the goal of delivering the message from one to another. It is essential that in mastering the translation lesson for the students to understand about the English text even both of an article or a book of science. This research aims to know the translation techniques applied by 4th-semester students at Peradaban University in translating final test text. This is qualitative research with a qualitative descriptive approach. The object of the research is 4th-semester students’ of Peradaban University. The data were analyzed by using translation techniques proposed by Molina and Albir. The analysis reveals that the most translation found was calque with 940 occurrences (62,37%), literal translation with 371 occurrences (20,90%), reduction with 96 occurrences (6,23%), and the last borrowing with 158 occurrences (10,48%). Based on the research result it can be concluded that students’ knowledge of translation techniques is very limited. In another word, in translating process they must master translation techniques to translate certain text, and know translation techniques to minimize translation errors in the translation product. This research will probably give some literature about the translation techniques that are applied in university students which can be applied by another researcher to conduct other research with another point of view. Also, for the lecturers it gives translation techniques materials with various techniques proposed by some experts.